i-ARKANUL Islam card / Mohd Khairul Sahrie Abdul Rashid and Wan Rohani Wan Abdullah - Abdul Rashid, Mohd Khairul Sahrie; Wan Abdullah, Wan Rohani (Universiti Teknologi MARA, Perak, 2020)
Student-centered learning is one of the elements in this 21st century learning. For Islamic Study subjects, entertaining lessons will attract students to be more focused. Thus, playing educational games can be one of the methods to obtain this approach. Therefore, i-Arkanul Islam Card was invented as a teaching aid for Islamic Study subject and as educational game. This card consists of 5 more small cards named I-Shahadah Card, I-Prayer Card, I-Fast Card, I-Zakat Card and I-Hajj Card. This card had been tested in a few selected schools. This card was also tested to a group of Islamic Education Teachers in Cameron Highlands district. As a result of the field study, I-Arkanul Islam Card successfully help pupils in mastering the basic facts contained in the Pillars of Islam. Feedbacks given by the Islamic Study teachers stated that this card is very helpful during the teaching and learning process in classes and very easy to be used. Plus, they also suggest that this innovation can be disseminated by doing content improvements.